Experimental Investigation on Potential Effect of Cell Shape and Size on the Residual Stress in Solid Oxide Fuel Cells - Azari, Khaled; Abdoli, Hamid; Torabi, Morteza; Bozorgmehri, Shahriar (Frontiers in Energy Research, 2022)
In the manufacturing process of solid oxide fuel cells (SOFCs), the residual stresses and curvature are developed in components due to the differences in material properties of cell layers. Residual stress may lead to the crack formation in the cell layers and facilitates cell fracture. In this work, the changes of the residual stress in the electrolyte layer of the anode-supported planar solid oxide fuel cells are experimentally determined at room temperature. The “sin2ψ” technique of X-ray diffraction method is employed to measure the residual stress in the half-cell samples. Investigation on the changes of the residual stress and curvature state in the scaling-up process of the cell is crucial for commercial use. Therefore, several cells with different sizes and shapes are investigated to evaluate the potential impact of cell size and cell shape on the residual thermal stress. Values of about −610 MPa are determined for the electrolyte layer on an oxidized ∼400 μm thick anode substrate. The results reveal that despite the effect of size and shape on the radius of curvature, these parameters have no significant impact on the residual stress level.